The Role of Technology in Enhancing Transparency and Accountability in Public Sector Organizations of Pakistan - Haque, Sirajul; Pathrannarakul, Pairote (International Journal of Economics, Business and Management Studies, 2013)
The wave of adoption of e-government technology is increasingly getting the momentum in the development countries for enhancing the good governance capability of public organizations. The research is aimed to analyze the impact of e-government technology in enhancing the Transparency and Accountability of public organizations. This research has taken the study of eight public organizations where e-government technology is used for enhancing transparency and accountability of public organizations. The research has been taken under two hypothesis related to transparency and accountability. In the context of transparency, it is hypothesized that instant information access positively affects in increasing the transparency of the organization and in the context of accountability, it is hypothesized that Empowerment of employees significantly increases accountability of the organization.